Assigning moral roles within the Second World War in Europe: National similarities, differences, and implications for group‐level moral representations. Issue 3 (18th December 2020) - Giner‐Sorolla, Roger; Hilton, Denis; Erb, Hans‐Peter; Durante, Federica; Flaßbeck, Christine; Fülöp, Eva; Mari, Silvia; Petrović, Nebojša; Sekerdej, Maciej; Studzinska, Anna; Skitka, Linda J.; Washburn, Anthony N.; et al.
Abstract : The moral roles assigned to nations that took part in the Second World War cast a shadow over contemporary international politics. To understand contemporary moral beliefs about the war, we took 11 mostly student samples from 9 nations that took part in the European theatre of war (total N  = 1, 427). We asked respondents, in free and scaled listings, to identify the war's heroes, villains, victims, and recipients of help. Nations and individuals seen as heroes, victims, and villains could be readily identified by most samples and showed both continuity and difference across nations. Most nations preferentially assigned themselves hero and victim roles, and the two were correlated positively, showing ingroup favouritism linked to victimhood. These findings show the importance of morality to contemporary views of the war and suggest further directions for studying today's political climate in Europe and elsewhere.